THE DIALECT WORD IN ITS FUNCTIONAL MANIFESTATIONS - Greshchuk, V. V.; Greshchuk, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article examines some peculiarities of the functioning of the dialect word, which have not been paid attention to in modern dialectology, and if they have been paid attention to, it is not enough. The purpose of the article is to highlight the semantic nuances of dialectisms, including the so-called contrastive ones in comparison with normative ones, to trace the specificity of dialect words in their functional manifestations in the Ukrainian literary language. Analytical-descriptive became the main method of researching the semantic paradoxes of a dialect word. The result of the scientific study was the expansion of the typology of dialectal lexical-semantic units, the identification, along with contrastive and non-contrastive dialectisms, of regional words, in the semantic structure of which two meanings are combined, one of which is literary standard, and the other is dialectal. It is also established how the area of the dialect, its territory, nature, landscape, inhabitants with their culture of economic activity, worldview determine the semantic space of the dialect vocabulary. An increase in the semantic-grammatical and functional properties of the dialect word was also revealed. The scientific novelty of intelligence lies in the fact that the materials analyzed in the article, the conclusions reached by the authors of the article, make it possible to supplement the typology of lexical-semantic dialectics, to interpret in a new way the conditioning of their functional manifestations by extra-linguistic factors. The obtained research results supplement modern dialectological studies on the typology of dialect vocabulary with new information about dialect vocabulary in its functional manifestations. The materials of the article can be used during the study of the course "Ukrainian dialectology" at the philological faculties of universities.